Land use policies and extension approaches for developing urban horticulture in Novi Sad - Hamid El Bilali; Biljana Panin; Siniša Berjan (Ekonomika Poljoprivrede (1979), 2010)
More than 50% of the Serbian population lives in urban areas that can provide multifunctional services and goods. Urban agriculture is about producing, processing and marketing food in cities and can help achieving urban ecosystems sustainability, improving urban residents living conditions and diversifying their income-generating activities. This review paper presents the state-of-the-art on urban agriculture in particular benefits; constraints and risks; production sites, systems, techniques and strategies; and some socio-economic and gender aspects. Extension services should develop new advisory and communication approaches to meet urban producers specific needs. Conducive land use and allocation policies, that can be designed and implemented to promote urban agriculture in Novi Sad, have been discussed.